The Impact of Internet Platforms on the Catering Industry - Li, Bowei (Transactions on Economics, Business and Management Research, 2024)
This paper aims to discuss the effects of Internet platforms on the catering business, particularly on food delivery services and online reviewing and booking platforms like Dianping and Meituan. In the light of the strategy and finance, this paper scrutinises these platforms to understand how they have transformed the restaurant sector, altered customer habits and affected the market. The paper aims at identifying and explaining the different roles that have been introduced in the market by these platforms and the effects that have come along with them. Furthermore, this paper is also an attempt to explore the possibility and threats of those new technologies to let people understand that restaurants must transform and change their strategies because the world is continuously advancing. Finally, the conclusion is made to demonstrate that restaurants have to become more digitised to sustain and thrive in this market. Embracing digital change is essential for future success.